Genetic and environmental influences on serum oxylipins, endocannabinoids, bile acids and steroids. (October 2021) - Bermingham, K.M.; Brennan, L.; Segurado, R.; Gray, I.J.; Barron, R.E.; Gibney, E.R.; Ryan, M.F.; Gibney, M.J.; Newman, J.W.; O'Sullivan, Dr. A.M.
Highlights: A classic twin study approach to modelling variation in lipid mediators including oxylipins, endocannabinoids, bile acids and steroids. Heritable lipid mediators included 12-HETE, 12-HEPE, 14-HDoHE and DHEA. 12-LOX derived lipid mediators are highly heritable. Environment contributes to a large proportion of variation for the majority of profiled lipid mediators. Abstract: Lipid bioactivity is a result of direct action and the action of lipid mediators including oxylipins, endocannabinoids, bile acids and steroids. Understanding the factors contributing to biological variation in lipid mediators may inform future approaches to understand and treat complex metabolic diseases. This research aims to determine the contribution of genetic and environmental influences on lipid mediators involved in the regulation of inflammation and energy metabolism. This study recruited 138 monozygotic (MZ) and dizygotic (DZ) twins aged 18–65 years and measured serum oxylipins, endocannabinoids, bile acids and steroids using liquid chromatography mass-spectrometry (LC-MS). In this classic twin design, the similarities and differences between MZ and DZ twins are modelled to estimate the contribution of genetic and environmental influences to variation in lipid mediators. Heritable lipid mediators included the 12-lipoxygenase products 12-hydroxyeicosatetraenoic acid [0.70 (95% CI: 0.12, 0.82)], 12-hydroxyeicosatetraenoic acid [0.73 (95% CI: 0.30, 0.83)] and 14‑hydroxy-docosahexaenoic acid [0.51 (95% CI: 0.07, 0.71)], along with the endocannabinoid docosahexaenoy-lethanolamide [0.52 (95% CI: 0.15, 0.72)]. For others such as 13-hydroxyoctadecatrienoic acid and lithocholic acid the contribution of environment to variation was stronger. With increased understanding of lipid mediator functions in health, it is important to understand the factors contributing to their variance. This study provides a comprehensive analysis of lipid mediators and extends pre-existing knowledge of the genetic and environmental influences on the human lipidome.